XPS and FT-IR Characterization of Selected Synthetic Corrosion Products of Zinc Expected in Neutral Environment Containing Chloride Ions - Juliusz Winiarski; Włodzimierz Tylus; Katarzyna Winiarska; Irena Szczygieł; Bogdan Szczygieł (Journal of Spectroscopy)
ZnO, Zn(OH)2, Zn5(OH)8Cl2·H2O, ZnCO3, and Zn5(CO3)2(OH)6 synthetic powders were prepared by chemical or solid-state method. Their crystalline phase structure, thermal behavior, and morphology were examined. Characteristic infrared absorbance bands were estimated by means of FT-IR ATR spectroscopy. X-ray photoelectron spectroscopy (XPS) allowed to calculate the modified Auger parameters (α ′) thereof to 2010.2, 2009.3, 2009.4, 2009.7, and 2009.8 eV, respectively for ZnO, Zn(OH)2, Zn5(OH)8Cl2·H2O, ZnCO3, and Zn5(CO3)2(OH)6. Finally, comparison of surface composition may be crucial to evaluation of the unknown experimental spectra of corrosion products formed on the surface of zinc alloy coatings exposed in NaCl solution.